An Adaptive Object Tracking Using Kalman Filter and Probability Product Kernel. (16th March 2016) - Ait Abdelali, Hamd; Essannouni, Fedwa; Essannouni, Leila; Aboutajdine, Driss
Abstract : We present a new method for object tracking; we use an efficient local search scheme based on the Kalman filter and the probability product kernel (KFPPK) to find the image region with a histogram most similar to the histogram of the tracked target. Experimental results verify the effectiveness of this proposed system.